The Clinical Utility of Virtual Reality in Neurorehabilitation: A Systematic Review. - Massetti, Thais; da Silva, Talita Dias; Crocetta, Tânia Brusque; Guarnieri, Regiani; de Freitas, Bruna Leal; Bianchi Lopes, Priscila; Watson, Suzanna; Tonks, James; de Mello Monteiro, Carlos Bandeira (Journal of Central Nervous System Disease, 2018)
Background: Virtual reality (VR) experiences (through games and virtual environments) are increasingly being used in physical, cognitive, and psychological interventions. However, the impact of VR as an approach to rehabilitation is not fully understood, and its advantages over traditional rehabilitation techniques are yet to be established. Method: We present a systematic review which was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). During February and March of 2018, we conducted searches on PubMed (Medline), Virtual Health Library Search Portal databases (BVS), Web of Science (WOS), and Embase for all VR-related publications in the past 4 years (2015, 2016, 2017, and 2018). The keywords used in the search were "neurorehabilitation" AND "Virtual Reality" AND "devices." Results: We summarize the literature which highlights that a range of effective VR approaches are available. Studies identified were conducted with poststroke patients, patients with cerebral palsy, spinal cord injuries, and other pathologies. Healthy populations have been used in the development and testing of VR approaches meant to be used in the future by people with neurological disorders. A range of benefits were associated with VR interventions, including improvement in motor functions, greater community participation, and improved psychological and cognitive function. Conclusions: The results from this review provide support for the use of VR as part of a neurorehabilitation program in maximizing recovery.